The Influence of Islamic Fundamentals Analysis on the Interest and Profitability of Sharia Stock Investors in KSPM-S East Java - Wahyunitasari, Eka Dita; Sopingi, Imam (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
This study analyzes the influence of Islamic-based fundamental analysis on the investment interest and profits of Islamic stock investors, particularly students who act as investors and are members of the Islamic Capital Market Study Group (KSPM-S) in East Java. The research is driven by the significance of Islamic financial literacy in supporting investment decisions that align with Islamic principles. A quantitative method with a path analysis approach is employed to identify the direct relationship between the understanding of Islamic fundamental analysis and the level of investment interest and resulting profits. The findings reveal that comprehension of core Islamic principles such as the prohibition of usury, the permissibility of business activities, and financial transparency has a positive impact on students’ interest in investing and contributes to increased investment returns. These results highlight the importance of integrating financial education with Islamic values in the investment decision-making process. The study also offers recommendations to enhance training programs on value-based Islamic stock analysis for the development of KSPM-S members.